Troels Fink: LandsbyfæHesskabet i Rinkenæs 1550-1769. (Skrifter udgivne af Historisk Samfund for Sønderjylland. Nr. 69, Aabenraa 1989). 104 s. - Stendal Pedersen, Finn (Historie/Jyske Samlinger, 1991)
-